The Information Society and Informatization Development Problems of Economy - Hafiiak, Alla; Borodina, Elena; Alyoshin, Sergei; Nosach, Oleksandr (International Journal of Engineering and Technology, 2018)
The article is devoted to the problem analysis of the information society development. The article explores the influence of the information component and general informatization processes on the national economy, its branches and individual enterprises, as well as strategic priorities of its development. Scientific and pedagogical literature was analyzed by the authors, on the basis of which it was concluded that the use of modern information technologies and software products developed on their basis is an urgent problem, the solution of which allows us to determine the promising directions of development in the economy and other areas.Analysis of the latest publications has shown that the countries with the developed information industry are the closest of all to the information society and the formation of the strategic foundations of the information economy, they develop and implement information public policy bringing investment and support of innovations in the information industry, in the development of computer systems and telecommunications and general informatization. The aim of the article is to study the problems of information society development, ways to solve them and the relationship with the processes of economy informatization. According to the purpose, the tasks were specified and fulfilled: the world experience in the information economy development was analyzed; the tasks of all states information programs that have embarked on the way of the society informatization were defined; the directions of the informatization influence (or information component) on the national economy were determined; the information about society features was systematized; the basic informatization principles were investigated. Nowadays, informatization should be aimed at increasing the efficiency of using the country's social, economic, scientific and technical potential, implementing mechanisms for the development of civilization in general, and being oriented towards meeting the information needs of all members of society.Â Â